Chiral nickel(II) and palladium(II) catalysts bearing strong electron‐withdrawing fluorine groups: synthesis, characterization and their application in catalytic polymerization for ethylene and styrene. (9th May 2014) - Yuan, Jianchao; Zhao, Jie; Song, Fengying; Xu, Weibing; Mu, Yanqiong; Chen, Jingjing; Zhang, Zhenghua
<x xml:space="preserve">Abstract</x> A series of new chiral and achiral nickel(II) and palladium(II) complexes, {bis[N, N′‐(2, 6‐diethyl‐4‐naphthylphenyl)imino]‐1, 2‐dimethylethane}dibromonickel 3a, {bis[N, N′‐(4‐fluoro‐2‐methyl‐6‐sec‐phenethylphenyl)imino]‐1, 2‐dimethylethane}dibromonickel rac‐(RS)‐3b, {bis[N, N′‐(4‐fluoro‐6‐sec‐phenethylphenyl)imino]‐1, 2‐dimethylethane}dibromonickel rac‐(RR/SS)‐3c and {bis[N, N′‐(4‐fluoro‐6‐sec‐phenethylphenyl)imino]‐1, 2‐dimethylethane}dichloropalladium rac‐(RR/SS)‐3d were successfully synthesized and characterized. The molecular structures of representative ligand rac‐(RS)‐2b, nickel complex 3a, rac‐(RR/SS)‐3c and palladium complex rac‐(RR/SS)‐3d were determined by X‐ray crystallography. The structures of complexes 3a and rac‐(RR/SS)‐3c have pseudo‐tetrahedral geometry about the nickel center, showing C2 molecular symmetry. However, the structure of palladium complex rac‐(RR/SS)‐3d has pseudo‐square planar geometry about the palladium center, showing C2 molecular symmetry. Complex 3e {bis[N, N′‐(2, 6‐dimethylphenyl)imino]‐1, 2‐dimethylethane}dibromonickel was also synthesized for comparison. Nickel complex rac‐(RS)‐3b bearing strong electron‐withdrawing fluorine group in the para‐aryl position and a chiral sec‐phenethyl group in the ortho‐aryl position of the ligand (one methyl group in the ortho‐aryl position) displays the highest catalytic activity for ethylene and styrene polymerization, and produced highly branched polyethylene and syndiotactic‐rich polystyrene. However, palladium complex rac‐(RR/SS)‐3d shows low catalytic activity for ethylene and styrene polymerization due to the poor leaving group, Cl, attached to palladium and the unfavorable molecular structure. Copyright © 2014 John Wiley & Sons, Ltd.